2013
DOI: 10.1111/jan.12136
|View full text |Cite
|
Sign up to set email alerts
|

An ethnographic study of the incentives and barriers to lifestyle interventions for people with severe mental illness

Abstract: This study provides evidence about the incentives and barriers to lifestyle interventions from service users' perspective, which should inform developments to improve the delivery of lifestyle interventions for this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(103 citation statements)
references
References 45 publications
7
93
0
3
Order By: Relevance
“…32 Second, families indicated that primary barriers to participation in or completion of a behavioral weight loss program were mostly related to psychiatric diagnosis or symptoms, as has been reported in adult mentally ill populations. 20,21,33 Caregivers also frequently cited a preference for in-session support to expose the child to new foods and PAs. Finally, pragmatic challenges with time management, costs, and transportation were cited as common barriers to participating in treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Second, families indicated that primary barriers to participation in or completion of a behavioral weight loss program were mostly related to psychiatric diagnosis or symptoms, as has been reported in adult mentally ill populations. 20,21,33 Caregivers also frequently cited a preference for in-session support to expose the child to new foods and PAs. Finally, pragmatic challenges with time management, costs, and transportation were cited as common barriers to participating in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Although the available evidence base in this area is limited, a small number of studies suggest that factors specifically related to psychiatric illness, including behavioral symptoms (e.g., social anxiety, paranoia, and lack of initiative), medication effects (sedation and excessive weight gain preventing physical mobility), and lack of transportation or social support often prevent mentally ill adults from engaging in weight loss treatment. 20,21 Programming that increases health knowledge and that offers social engagement and daily structure is cited as promoting engagement in behavioral weight loss programs. 22 There have been no published reports of behavioral weight loss interventions in antipsychotic treated youth, and no data are available regarding the preferences for and barriers to participating in behavioral weight loss interventions in this uniquely at-risk population.…”
mentioning
confidence: 99%
“…Out of a possible 106 articles identified by title, eleven articles met the inclusion criteria: Eight studies (Faulkner and Sparkes, 1999;Fogarty et al, 2005;Gorczynski et al, 2013;Johnstone et al, 2009;Leutwyler et al, 2013;Roberts and Bailey, 2013;Sandel, 1982;Weissman, 2006) considered the experiences of individuals with schizophrenia and three studies (Happell, 2012;Hedlund, 2013;Leutwyler et al, 2012) considered the experiences of HCPs. Figure 1 provides the results of the search within a PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flow diagram (Moher et al, 2009).…”
Section: The Systematic Searchmentioning
confidence: 99%
“…In recent years, interest has developed in understanding the experiences of people with schizophrenia of engaging in physical activity (Gorczynski et al, 2013;Leutwyler et al, 2013;Roberts and Bailey, 2013). Whilst ascertaining the view of the patient experience is clearly valuable, interest has also grown in ascertaining the views and experiences of health care professionals (HCPs) that implement physical activity in clinical practice (Leutwyler et al, 2012;Soundy et al, 2014;Stanton, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation